2010
DOI: 10.1095/biolreprod.110.085712
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Modifies Human Sperm Peroxiredoxins in a Dose-Dependent Manner

Abstract: Low levels of reactive oxygen species (ROS) modulate signaling pathways required for human sperm activation, but high levels impair sperm function, leading to infertility. Peroxiredoxins (PRDXs) are enzymes with a dual role as ROS scavengers and modulators of ROS-dependent signaling. The present study aimed to characterize PRDXs in human spermatozoa and possible modifications resulting from hydrogen peroxide (H(2)O(2)). We found PRDX1, PRDX4, PRDX5, and PRDX6 in both seminal plasma and spermatozoa. Using immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 75 publications
11
136
0
Order By: Relevance
“…It is noteworthy that the strong signal of tyrosine nitration and S-glutathionylation on the sperm head (Fig. 8) corresponds with the localization of PRDXs (O'Flaherty & de Souza 2011, O'Flaherty 2014. It is then plausible that the redox-dependent modifications of PRDXs are causing the increase in levels of sperm DNA damage observed in infertile men (Gong et al 2012).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It is noteworthy that the strong signal of tyrosine nitration and S-glutathionylation on the sperm head (Fig. 8) corresponds with the localization of PRDXs (O'Flaherty & de Souza 2011, O'Flaherty 2014. It is then plausible that the redox-dependent modifications of PRDXs are causing the increase in levels of sperm DNA damage observed in infertile men (Gong et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…PRDXs are highly abundant and differentially distributed in all sub-compartments of the human spermatozoon and are considered the first line of defense against oxidative stress in human spermatozoa (O'Flaherty & de Souza 2011). Our laboratory reported that PRDX1 and PRDX6 form w170 kDa protein complexes detected in spermatozoa treated with high concentrations of H 2 O 2 (0.25-5 mM) and also in spermatozoa from infertile men (O'Flaherty & de Souza 2011, Gong et al 2012. There is increasing evidence supporting the involvement of PRDXs in the regulation of redox signaling, especially H 2 O 2 -dependent signaling (Rhee et al 2005, Fourquet et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, high levels impair sperm function, leading to infertility. 45 High levels of showed an overexpression of this protein in the ERCR+ group vs. the ERCRÀ. Acrosomal biogenesis is divided into four different steps, Golgi, cap, elongation (acrosome), and maturation phases.…”
Section: +mentioning
confidence: 94%